PENERAPAN STRATEGI INQUIRING MINDS WHAT TO KNOW DALAM PEMBELAJARANMATEMATIKA SISWA KELAS VII SMPN 1 RANAH BATAHAN KABUPATEN PASAMAN BARAT - Asrialdi, Asrialdi; Rahmi, Rahmi; Anggraini, Villia (STKIP PGRI Sumbar, 2013)
Â Â Â Â Â The introduction of this research was caused by low mathematical of studentâs achievement at seventhÂ SMPN 1 Ranah Batahan. To solve the problem, the researcherÂ devoloved an inquiring minds what to know strategy. the aim of this research to know the studentâs mathematical achievement by using inquiring minds to know strategy is better than conventional strategy. the design of this research is experimental research. The population was takenÂ from seventh grade of studentâs at SMPN 1 Ranah Batahan academic year 2012/2013. The technique sampling of this research was random sampling and chosen VII.2 as experiment class and VIII.1 as control class. The instrumen was used test. In form essay with reability test =0,99. Technique of data analysis was used ttest one side. Based on the hypotesis testing was obtained P- value= 0,001 < Î±=0.05, so it can be concluded that studentâsÂ mathematical achievement by using inquiring minds what to know was better than conventional strategy.